FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK KESIAPSIAGAAN SECURITY TERKAIT KEBAKARAN DI TERMINAL PETI KEMAS SEMARANG PT. PELABUHAN INDONESIA III (PERSERO) - Tabita Kartikawati; Suroto Suroto; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Preparedness is the actions that enable governments, organizations, societies, communities and individual to be able to respond a disaster situation quickly and appropriately. Container terminal is classified as a workplace with heavy level of fire classification. Semarang Container Terminal has experienced incident of leakage of coconut oil that can trigger a fire. This study aims to analyze the relationship of age, work period, education level, knowledge, attitude, availability of fire protection, affordability of fire protection, firefighting training, supervision of OSH officers, peer support to the security preparedness practices related to fire at Semarang Container Terminals PT. Pelabuhan Indonesia III (Persero). The type of research used is descriptive-analytic with cross sectional approach. The sample used in this research is 67 people. The data were taken with questionnaire which has 62 questions. Based on bivariate analysis using Chi-Square test, it is showed that the variables related to are knowledge (p=0,046), attitude (p=0,017), firefighting training (p=0,008), and peer support (p=0,011). While unrelated variables are age, work period, education level, availability of fire protection, affordability of fire protection, and supervision of OSH officer. It can be concluded that knowledge, attitude, firefighting training, and peer support are related to security preparedness practices related to fire at Semarang Container Terminals PT. Pelabuhan Indonesia III (Persero).